Conceptual approaches to the complex of restoration of the affected territories as a result of military actions in Ukraine - Liudmyla Datsenko; Svitlana Titova; Marharyta Dubnytska (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The purpose of the study is to substantiate the conceptual approaches of the complex and to consider its main components regarding the restoration of territories affected by the war in Ukraine, with an emphasis on the incompleteness of current legal acts. It is therefore essential to develop new legal mechanisms that will ensure the procedure for removing contaminated lands into state ownership for their long-term restoration, with appropriate compensation to landowners for the period of time that the contaminated land remains in state ownership.